DAMPAK PENYETARAAN JABATAN TERHADAP MOTIVASI PEGAWAI DI KANTOR REGIONAL III BADAN KEPEGAWAIAN NEGARA BANDUNG - Juhendi, Hendi; Arundina Dijah Retno Pratiwi; Sait Abdullah (Jurnal Media Administrasi Terapan, 2025)
Bureaucratic reform, which is realized through a policy of simplifying organizational structures by equalizing positions from structural to functional, aims to optimize the effectiveness, efficiency and quality of public services. This research applies qualitative methods as an analytical framework. This research aims to describe and carry out an in-depth analysis of the phenomenon that is the object of study, namely employee motivation after the equalization of supervisory positions at the BKN Bandung Regional Office III. The findings of the motivational analysis of existence needs show that equalization of positions has caused changes in working conditions which are felt to decrease, especially in the material and facility aspects. Findings regarding the kinship needs of employees at Regional Office III BKN show a tendency to work individually, the loss of symbolic attributes from structural positions, and a reduction in structured communication patterns. There are still gaps in the need for growth in the career development system, transparency of training access and reward mechanisms. The conclusion of this research confirms that employee motivation after equalization of positions at Regional Office III BKN Bandung is influenced primarily by existence needs that have not been fully met. Compensation factors, facilities and work environment are fundamental aspects, while the relationship and growth dimensions still require strengthening so that optimal motivation is achieved.